PENGARUH KARAKTERISTIK BOARD OF COMMISIONERS TERHADAP CORPORATE SUSTAINABILITY PERFORMANCE DENGAN AUDIT COMMITTEE EXPERTISE SEBAGAI MODERASI - Hilya Auva Ulya (2023)
This research is a quantitative study with the aim of empirically proving the influence of the BOC size, president of BOC's education on corporate sustainability performance seen through economic, environmental and social aspects with the variable audit committee expertise moderating. This research uses secondary data obtained from annual reports and sustainability reports of non-financial companies on the Indonesia Stock Exchange (IDX) for 2019-2021. The sample in this study was 171 and the data was tested using the STATA version 17 application. The results showed that (1) BOC size has a positive and significant effect on corporate sustainability performance (economic, environment, social), (2) the president of BOC's education has no effect corporate sustainability performance (economic, environment, social). The results also state that (3) audit committee expertise cannot moderate the BOC size variable with corporate sustainability performance (economic, environment, social), (4) audit committee expertise cannot moderate the president of BOC's education variable with corporate sustainability performance (economic, environment, social).